1998
DOI: 10.1021/es980510h
|View full text |Cite
|
Sign up to set email alerts
|

Air Emissions from Exposed Contaminated Sediments and Dredged Material

Abstract: The sediment-to-air fluxes of two polycyclic aromatic hydrocarbons (phenanthrene and pyrene) and a heterocyclic aromatic hydrocarbon (dibenzofuran) from a laboratorycontaminated sediment and those of three polycyclic aromatic hydrocarbons (naphthalene, phenanthrene, and pyrene) from three field sediments were investigated in experimental microcosms. The flux was dependent on the sediment moisture content, air-filled porosity, and the relative humidity of the air flowing over the sediment surface. The mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…Low signatures were observed for explosives under all environmental conditions. Diffusion models, developed previously to predict polyaromatic hydrocarbon release from exposed dredged sediment, 13,14 were applied to simulate the explosives flux data satisfactorily with one fit parameter-soil to air partition constant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low signatures were observed for explosives under all environmental conditions. Diffusion models, developed previously to predict polyaromatic hydrocarbon release from exposed dredged sediment, 13,14 were applied to simulate the explosives flux data satisfactorily with one fit parameter-soil to air partition constant.…”
Section: Discussionmentioning
confidence: 99%
“…13 The test soils, spiked with the chemicals, were placed in the flux chamber in contact with air flowing over the soil surface. Stainless-steel air sampling traps containing 0.2 g Tenax TA (25-30 mesh) were attached to the exit ports of the chambers to collect explosive compounds released into the airstream.…”
Section: Experimental Section Uxo Transport Through Thin Uncontaminatedmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several ongoing studies on this issue of sediment aging and desorption and this matter remains to be resolved. 20,21 CONCLUSIONS Experimental data showed significant initial fluxes from both sediments upon resuspension and were directly related to suspended solids concentrations and air flow rate. Information about the scale of dredging and suspension volume is necessary to evaluate the air pollution potential.…”
Section: Comparison With Model Simulationmentioning
confidence: 95%
“…Valsaraj et al (1999) studied the air emissions from PAH-contaminated dredged sediment and found it to be dependent on soil moisture, the air-filled porosity and the relative humidity of the air. Miskewitz et al (2008) studied PCB emissions from dredged sediment in laboratory conditions and found that the addition of Portland cement decreased the time constant by a factor of 4 as compared to a non-treated sediment, i.e.…”
Section: Management and Remediation Of Contaminated Sediments And Assmentioning
confidence: 99%